Action research on implementing the BOPPPS model in teaching mechanical prophylaxis techniques for deep vein thrombosis - Mingyan Shen; Pengxia Wan; Zhixian Feng (BMC Nursing)
Abstract Objective To explore the application effects of the BOPPPS model in teaching mechanical prophylaxis techniques for deep vein thrombosis (DVT). Methods Following the “Plan-Act-Observe-Reflect” four-step process of action research, continuous improvements were made to the teaching process of DVT mechanical prophylaxis techniques based on the BOPPPS model. Data were collected by designated personnel and the teaching effectiveness was evaluated. Results Through three rounds of action research, the overall practical training scores for DVT mechanical prophylaxis techniques among students from the 2019–2021 cohorts were 84.45 ± 4.75, 88.43 ± 3.92, and 91.15 ± 4.58, respectively. The self-evaluation scores for DVT prophylaxis awareness were 95.93 ± 2.78, 97.39 ± 2.54, and 98.47 ± 2.47, all of which were statistically significant (P < 0.01). Cohen’s d effect sizes further confirmed substantial improvements. Conclusion Implementing the BOPPPS model in teaching DVT mechanical prophylaxis techniques helps improve students’ knowledge, skills, and prevention awareness. The action research method contributes to the standardization and scientific design of the curriculum.